The Religious Imagination and Contemporary Public Theology : Religijska imaginacija i suvremena javna teologija - Mocan, Beneamin (Array, 2021)
The process of secularization, known as the process of the privatization of religion or its denial from the public square, is a heritage of Modernity. This reality had (and continues to have) important consequences for Christian theology. Hence, the renewal of Christian theology is urgent, and has a lot at stake, especially regarding the need for a renewed Christian message within contemporary society. Though public theology appeared as a normal consequence of the need for the renewal of Christian theology, this renewal is not necessarily present in many of its methods. The rigidity of both of its theological methods and language remains a problem for public theology.  This article suggests that the new shift in anthropology should be taken into consideration when constructing a viable public theology nowadays.  The category of "religious imagination" is of utmost importance since it takes into consideration the new definition of the human being, which is in line more with postmodernism than modernity.  Thus, the article sketches the possible substantial contribution the religious imagination brings towards the revitalization of contemporary public theology. Moreover, the article mentions recent Romanian studies on the imagination, which stresses, even more, the richness hidden within it and its possible usage for the construction of a viable public theology.